Similarity search and applications : 7th International Conference, SISAP 2014, Los Cabos, Mexico, October 29-31, 2014. Proceedings - Traina, Caetano; Cordeiro, Robson Leonardo Ferreira; Traina, Agma Juci Machado (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 7th International Conference on Similarity Search and Applications, SISAP 2014, held in A Coruña, Spain, in October 2014. The 21 full papers and 6 short papers presented were carefully reviewed and selected from 45 submissions. The papers are organized in topical sections on Improving Similarity Search Methods and Techniques; Indexing and Applications; Metrics and Evaluation; New Scenarios and Approaches; Applications and Specific Domains.